Smart PMMA‑cerium oxide anticorrosive coatings: Effect of ceria content on structure and electrochemical properties - Harb, Samarah V. [UNESP]; Rodrigues, Mariana S. [UNESP]; de Souza, Thiago A.C. [UNESP]; Trentin, Andressa [UNESP]; Uvida, Mayara C. [UNESP]; Pochapski, Daniel J. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Hammer, Peter [UNESP] (Elsevier, 2021)
Organic-inorganic hybrids are considered an effective and environmentally compliant alternative to chromate-based anticorrosive coatings, currently banned due to the high toxicity of hexavalent chromium. In this work, hybrid nanocomposites based on poly(methyl methacrylate) (PMMA), covalently bonded to cerium oxide nanoparticles through the 2-hydroxyethyl methacrylate (HEMA) coupling agent, were tailored by carefully tuning the inorganic colloidal precursor to provide films with active corrosion protection for metallic substrates. Lithium hydroxide was exploited as oxidizing agent of cerium nitrate to form ceria nanoparticles. Precursor solutions and solid nanocomposites with different LiOH to Ce(NO3)3.6H2O molar ratios were analyzed using spectroscopic and electron microscopy techniques and theoretical simulations. Electrochemical impedance spectroscopy (EIS) was used to study the anticorrosive performance of the coatings on carbon steel and 7075 aluminum alloy. The results showed that increasing amounts of LiOH lead to the formation of higher ceria content and larger primary nanoparticles, ranging from 1.7 to 2.8 nm. The homogenous ~20 μm-thick coatings present excellent anticorrosive performance on carbon steel and AA7075 substrates. Coatings on carbon steel with low LiOH loading (1Li:1Ce) showed long-term durability and high impedance modulus of up to 29 GΩ cm2 after 1 day in saline solution. On the AA7075 alloy, the presence of larger cerium oxide particles at higher LiOH content (3Li:1Ce) acted as effective reservoirs of cerium ions, providing high barrier coatings (395 GΩ cm2) with active corrosion protection.
Keywords: Cerium oxide nanoparticle; Corrosion protection; Organic-inorganic coating; PMMA‑cerium oxide hybrid; Smart coating